Incidence of measles specific IgG antibody among children in Adamawa State, Nigeria - Isa, H.; Ja’afaru, M. I.,; Bashir, M.; Iliyasu, A. (UMYU Journal of Microbiology Research)
Measles account for nearly half of the 1.7 million annual deaths due to childhood vaccine- preventable diseases. Presence of measles specific IgG antibodies has been proven to correlate with protection (immunity) to natural measles infection. This study was therefore designed to determine the prevalence of measles specific IgG antibody and also to determine the association between prevalence of measles specific IgG antibody and age, gender, as well as history of measles infection among children aged 0-14 years in Adamawa State. The research was carried out within the three senatorial districts of the State. Serum samples (368) collected from children were used to determine the prevalence using ELISA method. Questionnaire was used to obtain demographic data of the children relevant to the study. The study revealed that 227 (61.6%) of the children had protective measles IgG antibody with antibody titre ranging from 10-250 U/mL, while 141 (38.4%) had non-protective measles IgG antibody. There was significant association between history of measles infection and protective antibodies (P-value=0.000), but there was no significant association between gender (P-value = 0.958), age (P- value = 0.140) and protective measles IgG antibody.